Entre o desenvolvimento econômico e a preservação ambiental: O caso da pesca artesanal e a configuração de um cenário de injustiça ambiental em Regência Augusta - ES. - Leonardo, Flávia Amboss Merçon (2014)
This work starts with a reflexion on Espirito Santo's present economic conjuncture, which has been figuring out as a major commodities' producer and exporter. Over the last years, its coastal range has become a space of massive interventions from these activities, specially those related to mining, cellulose, oil and gas, besides port infrastructure. Regarding this picture, the main objective of this research is to understand how local groups, most times undermined by these economic activities and highly dependant on the environment to keep their cultural and social traditions, are living under the social transformations that have been going on on their living and working sites. The district of Regência Augusta in the city of Linhares-ES was choosen as the empirical site of the study field, for it simultaneously serves as a stage for development actions (linked to oil and gas) as well as conservational ones (Conservancy Units; the Tamar Project), which have been coexisting with the local artisan fishing. As for the specific objectives, we intend to understand how fishermen and artisan fishermen on that site are living and perceiving the social change processes, mainly within the fishing activity, caused by these developing and conservational activities.